Ergonomics risk assessment among support staff in Universiti Malaysia Pahang - Faisal, Jusoh; M. Nafis, O. Z. (IOP Publishing, 2018)
Awareness of ergonomic risk assessment among workers are getting intense in many industries nowadays. It is essential since most of the workers spend 7 to 8 hours of their time in the workplaces. Previous study shown that spending too much time with static posture in sitting at workplace leads to the problem of Musculoskeletal Disorders (MSDs). The implications are not only harmful to human body but also effect the productivity. Currently, there are no scientific study conducted to assess the conditions of workers in Universiti Malaysia Pahang (UMP). Therefore, the problem of MSDs could not be justified clearly and the top management did not acknowledge this issue. This study aims to present current scenario of ergonomic risk level at UMP by using structured model. It focuses on operational staff from faculties and Human Resources Department (HRD). Initially, three types of assessments are executed based on general working condition, Cornell Muscokeletal Discomfort Questionnaire (CMDQ) and Rapid Office Strain Assessment (ROSA). Based on the findings, 90% of the respondents felt discomfort at workplace but prefer to rectify the issues by themselves. Almost 50% of them evaluated themselves in level 4-5 of discomfort level. The CMDQ result shown the discomfort area at faculties and HRD. The workplace at faculties and HRD had been assessed through ROSA and the overall result shown the risk level is medium level respectively. Therefore, further investigation is requires and improvement of workplace need to be proposed to establish good working condition.